The role of swimming and pool exercises in the correction of postural defects - Lassek, Bartłomiej (Physical education, sport and olympism from a pedagogical perspective, 2023)
The article covers theoretical considerations of the role of swimming and water exercises in the correction of postural defects. It discusses the factors affecting the human body while in the water, issues in the field of postural defects that occur, basic ways of diagnosing postural defects, exercises to prepare for exercises in water on land, elements of classification of exercises in corrective swimming and their brief characteristics. A study by another author on the effect of competitive swimming on the correction of postural defects is cited. Additionally, for the purpose of this article other authors’ study on the postural defects caused by the type of work and factors resulting from COVID-19 pandemic were used. The method of document analysis was used for the study, so the literature was reviewed. An attempt was made to answer the research question: do swimming and water exercises play an important role in the correction of postural defects? The research is a pilot study. The results of the study cover conclusions obtained from the analysis of available documents.